Customer satisfaction and its measurement in hospitality enterprises: a revisit and update. Issue 1 (11th January 2016) - Pizam, Abraham; Shapoval, Valeriya; Ellis, Taylor
Abstract : Purpose: This paper aims to review and discuss customer satisfaction and its application to the hospitality and tourism industries. This paper defines the concept and analyzes its importance to services in general and to hospitality/tourism services in particular. This paper is a revision and update of an article previously published by Pizam and Ellis (1999) on customer satisfaction measurements. Design/methodology/approach: The most recent research on customer satisfaction measurements and scales is summarized and presented in the paper. Findings: Following a discussion on the dimensions and attributes of satisfaction, the main methods of measuring satisfaction are listed, and cross-cultural issues that affect satisfaction are reviewed. Finally, the paper concludes with a comprehensive review of the current online tools and techniques available for measuring customer satisfaction. Research limitations/implications: This summary gives a good overview to researchers who require a comprehensive review of the available research measurements and scales for customer satisfaction. Originality/value: For the past decade, a considerable amount of research has been conducted in customer satisfaction. Finding the appropriate measurements and scales for customer satisfaction can be time-consuming and confusing. This paper provides a comprehensive overview of the best-known measurements and scales in customer satisfaction research. The paper also provides innovative online tools and techniques available for research.